Numerical Analysis of the Characteristics of the Heat Treatment Process of Multilayer Composite Products in Heat Technology Installations - V. N. Romaniuk; A. M. Niyakovskii; A. N. Chichko; Yu. V. Yatskevich; Т. N. Ryzhova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
. The results of numerical studies carried out on the basis on a mathematical model developed by the authors of this paper devoted to the investigation of the influence of various factors on the characteristics of the process of heat treatment of composite products in industrial heat technology installations in the presence of internal heat emissions distributed over the volume of individual layers of the product are presented. The formulation of boundary conditions for this model is proposed, considering the multilayer structure of products and the peculiar properties of the organization of their heat treatment process in a heat technology installation. A detailed description of the mathematical model was presented in the previous works. In this study, the functions of temperature distribution and the coefficient (degree) of hydration in the spatial regions that make up the product have been studied as characteristics of the heat treatment process. Model composite products of the same shape and structure but of different volume, consisting of two layers of material in which an exothermic hydration reaction takes place separated by a layer of expanded polystyrene were considered. The temperature-time regime of heat treatment was assumed to be close to that used in industrial conditions in the production of three-layer external wall panels. The boundary and initial conditions corresponded to the conditions of heat treatment on flat stands with water heating and sheltering products from above. It has been determined that the presence of a thermal insulation layer in the core of the product separating the layers that have an internal heat source, changes the distribution of temperature values and the hydration coefficient in the upper and lower layers significantly. An increase in the characteristic volume of the product leads to an increase in the influence of internal volumetric heat release on the processes of heating and hydration, while heat release caused by the course of the hydration reaction begins to have a decisive influence on them.